Efficacy and safety of perampanel in epilepsy: A systematic review and meta-analysis of randomised controlled trials. (November 2022) - Lavu, Alekhya; Aboulatta, Laila; Abou-Setta, Ahmed M.; Aloud, Basma; Askin, Nicole; Rabbani, Rasheda; Shouman, Walid; Zarychanski, Ryan; Eltonsy, Sherif
Highlights: This systematic review reports significant reduction in seizures and a potential dose-based increase in discontinuations due to TEAE. When compared with placebo, both 8 mg and 12 mg doses of perampanel showed similar efficacy in seizure control. A higher risk of treatment discontinuation was found among 12 mg users than among 8 mg users. The most reported TEAEs were non-threatening, with the potential possibility of rare but serious adverse psychological outcomes. Further comparative effectiveness trials – as well as longitudinal follow-up observational studies – are needed to decide on the optimal doses for epilepsy management with perampanel. Abstract: Background: Perampanel a third-generation antiseizure medication, belongs to a new promising class of drugs called AMPA receptor antagonists, approved to treat focal-onset seizures with or without focal to bilateral tonic clonic seizures and primary generalized tonic-clonic seizures. Methods: This review included RCTs on patients with epilepsy exposed to perampanel compared with placebo, or one or more pre-existing antiseizure medications. Four databases and two clinical trial registries were searched from inception to July 2021. Included outcomes were 50% responder rate, seizure-free rate, discontinuation due to treatment-emergent adverse events (TEAE)s, having any TEAEs, and most reported TEAEs. Cochrane risk of bias tool was used to assess the internal validity of the included RCTs. Results: From 2211 retrieved citations, eight RCTs were included in the meta-analysis. Fifty-percent responder and seizure freedom rates were significantly higher in patients receiving perampanel when compared to placebo (RR 1.57, 95 % CI 1.35 to 1.82, I 2 15% and RR 2.79, 95% CI 1.58 to 4.93, I 2 7%, respectively). The 50% responder rates for 8mg and 12 mg, when compared to placebo, were similar. The most-reported TEAEs were dizziness and somnolence with <1% reporting serious psychological outcomes. Conclusion: This systematic review reports significant reduction in seizures and a potential dose-based increase in discontinuations due to TEAE. The most-reported TEAEs were non-threatening, with the possibility of rare but serious adverse psychological outcomes. Further independent RCTs studying the most efficient dose for efficacy and safety are needed.